Training of Military Personnel in First AID Based on Innovative Approaches - Nishanbayevich, Djumashev Alisher (International Journal on Integrated Education, 2023)
The article discusses innovative approaches in teaching first aid skills to military personnel. Active teaching methods are offered, using simulation equipment and psychological training. Special importance is given to simulation training methods, which allow military personnel to form the necessary competencies.